Heuristics and meta-heuristics for lot sizing and scheduling in the soft drinks industry: a comparison study - Ferreira, D.; Franca, P. M. [UNESP]; Kimms, A.; Morabito, R.; Rangel, S. [UNESP]; Toledo, C. F. M.; Xhafa, F; Abraham, A (Springer, 2008)
This chapter studies a two-level production planning problem where, on each level, a lot sizing and scheduling problem with parallel machines, capacity constraints and sequence-dependent setup costs and times must be solved. The problem can be found in soft drink companies where the production process involves two interdependent levels with decisions concerning raw material storage and soft drink bottling. Models and solution approaches proposed so far are surveyed and conceptually compared. Two different approaches have been selected to perform a series of computational comparisons: an evolutionary technique comprising a genetic algorithm and its memetic version, and a decomposition and relaxation approach.
Keywords: Two-level Production Planning; Lot Sizing; Scheduling; Soft Drinks Industry; Genetic Algorithm; Memetic Algorithm